Controlling of jerk chaotic system via linear feedback control strategies - Karam Adel Abed (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In this paper, the strategies of linear feedback control for jerk system is considered. These strategies consist  of four strategies (ordinary feedback control, dislocated feedback control,  speed feedback control, and  enhancing feedback control). We propose to  combine between these   strategies and obtained a better result  from this combine. Numerical solution achieved the same results.